Current Indications for Surgical Repair in Patients with Bicuspid Aortic Valve and Ascending Aortic Ectasia. (20th September 2012) - Etz, Christian D.; Misfeld, Martin; Borger, Michael A.; Luehr, Maximilian; Strotdrees, Elfriede; Mohr, Friedrich-Wilhelm
Abstract : Preventive surgical repair of the moderately dilated ascending aorta/aortic root in patients with bicuspid aortic valve (BAV) is controversial. Most international reference centers are currently proposing a proactive approach for BAV patients with a maximum ascending aortic/root diameter of 45 mm since the risk of dissection/rupture raises significantly with an aneurysm diameter >50 mm. Current guidelines of the European Society of Cardiology (ESC) and the joint guidelines of the American College of Cardiology (ACC)/American Heart Association (AHA) recommend elective repair in symptomatic patients with dysfunctional BAV (aortic diameter ≥45 mm). In asymptomatic patients with a well-functioning BAV, elective repair is recommended for diameters ≥50 mm, or if the aneurysm is rapidly progressing (rate of 5 mm/year), or in case of a strong family history of dissection/rupture/sudden death, or with planned pregnancy. As diameter is likely not the most reliable predictor of rupture and dissection and the majority of BAV patients may never experience an aortic catastrophe at small diameters, an overly aggressive approach almost certainly will put some patients with BAV unnecessarily at risk of operative and early mortality. This paper discusses the indications for preventive, elective repair of the aortic root, and ascending aorta in patients with a BAV and a moderately dilated—or ectatic—ascending aorta.